Reception of Audiences Aged 8–15 Years to Gimmick and Sarcasm in Windah Basudara's YouTube Content - M. Gibran Pratama, Gibran; An Nur, Fitrinanda (Jogjakarta Communication Conference (JCC), 2025)
This study explores the audience reception of children and early teenagers (ages 8–15) toward YouTube content by Windah Basudara, known for his sarcastic style and repeated use of gimmicks. Using digital observation and content analysis methods, this research investigates how young viewers interpret media messages and how viral trends like “Brainrot” influence their media consumption behavior. Based on Stuart Hall’s encoding/decoding theory, findings indicate that young audiences tend to accept meanings hegemonically without critical reflection. These results highlight the urgent need for digital media literacy education at an early age.